On Stock Operations in Retail Stores with Backyard - MASUDA, Etsuo; YAN, Chunrong (Journal of Japan Logistics Society, 2008)
The stock operation with less personnel expenses and more consumer satisfaction is an important subject in the retail stores. In this paper, we have selected the retail stores with backyard for study and have proposed an efficient interaction mechanism between store personnel and a stock data management system as well as the method of the optimum stock sharing with the selling place.